Comparison of Faecal Microbial Community of Lantang, Bama, Erhualian, Meishan, Xiaomeishan, Duroc, Landrace, and Yorkshire Sows - Yang, Lina (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2014)
The objective of this study was to investigate differences in the faecal microbial composition among Lantang, Bama, Erhualian, Meishan, Xiaomeishan, Duroc, Landrace, and Yorkshire sows and to explore the possible link of the pig breed with the gut microbial community. Among the sows, the Meishan, Landrace, Duroc, and Yorkshire sows were from the same breeding farm with the same feed. Fresh faeces were collected from three sows of each purebred breed for microbiota analysis and volatile fatty acid (VFA) determination. Denaturing gradient gel electrophoresis (DGGE) analysis revealed that samples from Bama, Erhualian, and Xiaomeishan sows, which from different farms, were generally grouped in one cluster, with similarity higher than 67.2%, and those from Duroc, Landrace, and Yorkshire sows were grouped in another cluster. Principal component analysis of the DGGE profile showed that samples from the foreign breeds and the samples from the Chinese indigenous breeds were scattered in two different groups, irrespective of the farm origin. Faecal VFA concentrations were significantly affected by the pig breed. The proportion of acetate was higher in the Bama sows than in the other breeds. The real-time PCR analysis showed that 16S rRNA gene copies of total bacteria, Firmicutes and Bacteroidetes were significantly higher in the Bama sows compared to Xiaomeishan and Duroc sows. Both Meishan and Erhualian sows had higher numbers of total bacteria, Firmicutes, Bacteroidetes and sulphate-reducing bacteria as compared to Duroc sows. The results suggest that the pig breed affects the composition of gut microbiota. The microbial composition is different with different breeds, especially between overseas breeds (lean type) and Chinese breeds (relatively obese type).